Prominent IgE-binding and cytokine-inducing capacities of a newly cloned N-terminal region of Der f 14, an apolipophorin-like house dust mite allergen. (11th September 2017) - ElRamlawy, Kareem Gamal; Fujimura, Takashi; Aki, Tsunehiro; Okada, Akiyasu; Suzuki, Takayuki; Abe, Takuya; Hayashi, Takaharu; Epton, Michael J; Thomas, Wayne R; Rafeet, Inas Hussein; Al-Azhary, Diaa Beshr; Ono, Kazuhisa; et al.
Abstract: We previously characterized a 177-kDa allergen, M-177, from Dermatophagoides farinae . Thereafter, a counterpart to M-177 for Euroglyphus maynei was cloned as Eur m 14, and its sequence revealed that two environmental allergens, Mag 1 and Mag 3, are digested fragments of M-177. The aims of this study were to clone the cDNA of Der f 14 corresponding to M-177 and to elucidate the allergenic capacities of the N-terminal fragment of Der f 14 (Der f 14-N). Recombinant allergens were produced as trigger-factor-fused proteins in Escherichia coli . Der f 14-N showed the highest IgE-binding frequency among Der f 14-derived fragments in patients allergic to house dust mite by enzyme-linked immunosorbent assay. Der f 14-N showed the highest capacity to induce cell proliferation in murine lymphocyte and human peripheral mononuclear cells among Der f 14-derived fragments. Der f 14-N induced IL-13, IFN-γ and IL-17 production more than Der f 1 and Der f 2 in mouse, and induced IL-5 and IFN-γ production at levels comparable to those of Der f 1 and Der f 2 in some patients. The high prevalence of IgE binding to the Der f 14-N indicates that it could be an important mite allergen.